Neonatal vitamin A supplementation associated with increased atopy in girls. Issue 8 (18th May 2015) - Aage, S.; Kiraly, N.; Da Costa, K.; Byberg, S.; Bjerregaard‐Andersen, M.; Fisker, A. B.; Aaby, P.; Benn, C. S.
Abstract Background Neonatal vitamin A supplementation (NVAS) is currently being considered as policy in countries at risk of deficiency. A previous study suggested that NVAS may be associated with increased atopy. We examined the effect of NVAS on atopy by conducting long‐term follow‐up of a previous randomized controlled trial in Guinea‐Bissau. Methods In 2002–2004, we randomized 4345 normal birthweight neonates to NVAS (50 000 IU retinyl palmitate) or placebo together with their Bacillus Calmette–Guérin vaccination. In 2013, we visited the 1692 (39%) children now aged 8–10 years who were still living in the study area, and 1478 (87%) were found at home. Provided consent, a skin prick test was performed, and history of allergic symptoms was recorded. Associations of NVAS and atopy (defined as skin prick test reaction of ≥3 mm) were analysed using binomial regression. Results Of the 1430 children with a valid skin prick test, 228 (16%) were positive (more boys (20%) than girls (12%), P‐value < 0.0001). NVAS did not increase the overall risk of atopy (RR 1.10 [95% CI 0.87–1.40]). However, NVAS was associated with significantly increased risk among females (RR 1.78 [1.17–2.72]) but not among males (0.86 [0.64–1.15], P‐value for interaction between NVAS and gender = 0.005). Furthermore, NVAS was associated with increased risk of wheezing among females (RR 1.80 [1.03–3.17], but not among males, P‐value for interaction = 0.05). Conclusion The study corroborated previous observations; NVAS was associated with increased risk of atopy and wheezing, in this study only among females. Further studies on NVAS and atopy are warranted.